Identification and exploration of the potential antiaging role of the novel antioxidant peptide DGGY derived from yak milk proteins - Rubin Wang; Zhandu Danzeng; Jinyong Yang; Jiu Qu; Ruikai Zhu; Huanhuan Li; Honggang Tang; Caiyan Li; Ke Zhao (Journal of Dairy Science)
ABSTRACT: Yak milk has substantial nutritional value yet remains underutilized for high-value applications. Because yak milk is a rich source of bioactive peptides due to its elevated protein composition, this study investigated yak milk-derived peptides with antioxidant properties and their potential antiaging mechanisms. First, 8 major yak milk proteins were hydrolyzed in silico via BIOPEP. Compared with other enzymes, proteinase K plus subtilisin could generate more antioxidant peptides. Six potential antioxidant peptides were efficiently screened in silico; DGGY presented the strongest hydroxyl radical scavenging rate, and its antioxidant activity was further verified in Caenorhabditis elegans. Additionally, the results of network pharmacology analysis suggested an antiaging role of DGGY, which was validated in C. elegans; specifically, supplementation with DGGY (50 and 300 μg/mL) significantly extended the life span of C. elegans by regulating the expression of related genes (including sod-3, snk-1, daf-16, daf-2, and hsp-16.2). In summary, a novel yak milk protein-derived antioxidant peptide, DGGY, was efficiently screened and found to exert potential antiaging effects. This study provides a method for the high-value utilization of yak milk and novel information for antiaging research.